Is There Such Thing As Middle Class Values? Class Differences, Values and Political Orientations in Latin America - Lopez-Calva, Luis F.; Rigolini, Jamele; Torche, Florencia (2012)
Middle class values have long been perceived as drivers of social cohesion and growth. This paper investigates the relation between class (measured by position in the income distribution), values, and political orientations using comparable values surveys for six Latin American countries. The analysis finds that both a continuous measure of income and categorical measures of income-based class are robustly associated with values. Both income and class tend to display a similar association to values and political orientations as education, although differences persist in some important dimensions. Overall, there is no strong evidence of any "middle class particularism": values appear to gradually shift with income, and middle class values are between the ones of poorer and richer classes. If any, the only peculiarity of middle class values is moderation. The analysis also finds changes in values across countries to be of much larger magnitude than the ones dictated by income, education, and individual characteristics, suggesting that individual values vary primarily within bounds dictated by each society.